SOLUTION OF THE CAUCHY PROBLEM FOR A DEGENERATE PARABOLIC EQUATION - Hovhannisyan, A. H.; Rafayelyan, S. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
Using the Mellin transformation the solution of the Cauchy problem for one type degenerate a parabolic equation is constructed.